Physics of ZnO/SiO2 electrolyte semi-conductive thermal electric generator - Rahman, Mohammed Ataur; Aung, Kyaw Myu; Saifullah, Khalid; Rahman, Mizanur (Institute of Advanced Science Extension (IASE), 2017)
Thermoelectric generator generates electrical power from heat based on the temperature gradient. The total energy (fuel) supplied to the engine, approximately 30 to 40% is converted into useful mechanical work, whereas the remaining is expelled to the environment as heat through exhaust gases and cooling systems, resulting in serious greenhouse gas (GHG) emission. The technologies reported on waste heat recovery from exhaust gas of internal combustion engines (ICE) are thermo electric generators (TEG) with finned type, Rankine cycle (RC) and Turbocharger by the different researchers. The deficiency and acclimatization of existing TEG emphasis this study to develop a nanomaterial zinc oxide (ZnO)/Silicon di-oxide (SiO2) electrolyte based semi-conductive thermal electric generator (TEG) to generate electricity from the IC engine exhaust heat. This technology produces electricity from the exhaust heat due to the thermal motion, carrier drift and carrier diffusion. The ZnO/SiO2 simulated result based on the 60% of exhaust heat of IC engine shows that its electrical energy generation is about 80% more than conventional TEG for the exhaust temperature of 500C due to its higher thermal and electric conductivity and higher surface area both in radially and longitudinally. The ZnO/SiO2 electrolyte semi- conducive technology develops 524W to 1600W at engine speed 1000 to 5000 rpm, which could contribute to reduce the 10-12% of engine total fuel consumption and improve emission level by 20%.